Assessing the causal association of sleep abnormalities with preeclampsia and eclampsia: a Mendelian randomization analysis - Juan Li; Yuling Kong; Guosu Shi; Shuxiao Dong; Xueying Wang; Li Feng; Quanzhou Guo; Caihong Lu (Hypertension in Pregnancy)
Background Preeclampsia and eclampsia are severe pregnancy disorders marked by hypertension and potential organ damage. The etiological basis of preeclampsia and eclampsia is not fully understood. Previous studies have revealed a link between sleep abnormality and preeclampsia/eclampsia, but the causal relationship remains unclear. In this study, we explored the genetic links between sleep and preeclampsia/eclampsia using genome-wide association study (GWAS) summary data and Mendelian randomization (MR) analysis.Methods RNA sequence dataset GSE114691 was downloaded from the Gene Expression Omnibus database, comprising placental tissues from patients with preeclampsia and controls. Differential expression analysis was conducted with R (v4.2.3) and DESeq2 (v1.38.3). Gene set enrichment analysis (GSEA) was carried out using HTSanalyzeR2. GWAS summary data on preeclampsia/eclampsia and genetic markers for sleep abnormality were sourced from the FinnGen Consortium and IEU genetic databases. The Mendelian randomization analysis was conducted with TwoSampleMR (v0.6.2), and the inverse variance weighted (IVW) approach was employed as the principal method.Results GSEA analysis revealed that the orexin receptor pathway showed heightened expression in the preeclampsia group versus controls. The random-effects IVW results showed that sleeplessness/insomnia has a genetic causal relationship with preeclampsia (OR = 2.08, 95% CI: 1.07–4.06, p = 0.0318), while sleep duration has evidence of regulating eclampsia (OR = 0.09, 95% CI: 0.01–0.67, p = 0.0187).Conclusion This study provides significant evidence for a genetic causal association between sleep abnormalities and preeclampsia/eclampsia. [Figure: see text]